Violence against emergency medical services personnel: A systematic review of the literature - Maguire, Brian J.; O'Meara, Peter; O'Neill, Barbara J.; Brightwell, Richard (American journal of industrial medicine, 2018)
Background Violence against emergency medical services (EMS) personnel is a growing concern. The aim of this systematic review is to synthesize the current literature on violence against EMS personnel. Methods We examined literature from 2000 to 2016. Eligibility criteria included English‐language, peer‐reviewed studies of EMS personnel that described violence or assaults. Sixteen searches identified 2655 studies; 25 studies from nine countries met the inclusion criteria. Results The evidence from this review demonstrates that violence is a common risk for EMS personnel. We identified three critical topic areas: changes in risk over time, economic impact of violence and, outcomes of risk‐reduction interventions. There is a lack of peer reviewed research of interventions, with the result that current intervention programs have no reliable evidence base. Conclusions EMS leaders and personnel should work together with researchers to design, implement, evaluate and publish intervention studies designed to mitigate risks of violence to EMS personnel.